Impact of Digital Leadership and Organizational Intelligence on Digital Organizational Transformation: An Empirical Study - Dedeoğlu, İzzet; Ak, Murat; Demir, Filiz; Uysal, H.Tezcan (Makara Human Behavior Studies in Asia, 2026)
Technological and digital developments in the current information age have brought profound transformations to organizations, especially business operations and structures. Digital organizational transformation may be more effectively managed through the combined influence of digital leadership and organizational intelligence. This study examines the impact of digital leadership and organizational intelligence on the digital organizational transformation process, addressing a clear gap in the existing literature, as few studies have empirically investigated these factors together. Data were collected via an online survey from 104 employees of a packaging company in Konya, Türkiye, using a convenience sampling method. The study was designed as an explanatory quantitative research, and the data were analyzed using SPSS version 27. To test the hypotheses, descriptive statistics, reliability analyses, normality tests, correlation, and multiple regression analyses were conducted. The findings indicate significant positive relationships among digital leadership, organizational intelligence, and digital organizational transformation, suggesting that organizations with higher levels of organizational intelligence adapt more rapidly to digital transformation processes. From a practical perspective, managers can enhance their digital leadership competencies through data-driven decision-making, agile management practices, and fostering a digital innovation culture. Furthermore, strengthening organizational intelligence through systematic knowledge-sharing, cross-functional collaboration, and continuous learning initiatives can accelerate and sustain digital organizational transformation efforts. These results provide empirical evidence for integrated strategies that combine leadership capabilities and organizational intelligence to support organizations’ effective digital transformation.